Discontinuation of octreotide LAR after long term, successful treatment of patients with acromegaly: is it worth trying? - Ramírez, C; Vargas, G; González, B; Grossman, A; Rábago, J; Sosa, E; Espinosa-de-Los-Monteros, A; Mercado, M (2012)
BACKGROUND: Somatostatin analogs (SA) have been used for over 25 years in the treatment of acromegaly. A major disadvantage is the need to continue therapy indefinitely. OBJECTIVE: To evaluate the feasibility of discontinuing therapy in well-controlled patients with acromegaly treated chronically with SA. DESIGN AND METHODS: Of the 205 subjects on octreotide LAR, we selected those who met the following criteria: two or more years of treatment, a stable dose and injection interval of 20  mg every 8 weeks or longer for the previous year, no history of radiation, no cabergoline for the previous 6 months, a GH <1.5  ng/ml, and an IGF1 <1.2×upper limit of normal (ULN). Octreotide LAR was stopped and both GH and IGF1 were measured monthly for 4 months; a glucose-suppressed GH value and magnetic resonance imaging were obtained at the 4th month, thereafter, basal GH and IGF1 were measured q. 3 months, for 12-18 months. Patients were removed from the study if GH or IGF1 rose to 1.5  ng/ml or 1.2×ULN respectively. RESULTS: Twelve patients (ten women, mean age 48±13 years) were studied. Seven patients (58.3%) relapsed biochemically within 1 year of having stopped the SA; two patients relapsed by GH and IGF1 criteria, the remaining five patients kept GH levels within target. Five patients (41.7%) remain in remission after 12 months of follow-up. Non-recurring patients were on longer injection intervals but no other characteristic was associated with a successful withdrawal. CONCLUSION: Withdrawal of SA is possible in a small but distinct subset of patients, particularly in those who are very well controlled on relatively low doses administered at long intervals.